Spuriously low thyroid-stimulating hormone? A laboratory phenomenon - S Danalakshmi; Mamta Soni (Apollo Medicine)
Thyroid gland is an endocrine gland with vital functions regulating metabolism, growth, and development. The tests used to assess the functions of the thyroid gland include thyroid-stimulating hormone (TSH), free thyroxine, and free tri-iodothyronine. TSH is routinely measured in the clinical laboratory with automated immunoassays to diagnose and monitor thyroid disorders. We present a case wherein the discrepancy between the clinical symptoms and the biochemical test results raised the possibility of methodological interference in laboratory testing, finally leading to a detection of a rare genetic mutation in the patient. This case reiterates that clinical correlation of laboratory results and effective communication between the clinician and the laboratory are imperative for a correct diagnosis and therapeutic interventions.